Polyurethane/Polylactide-Based Electrospun Nonwovens as Carriers for Human Adipose-Derived Stromal Stem Cells and Chondrogenic Progenitor Cells. (11th December 2016) - Marycz, Krzysztof; Marędziak, Monika; Grzesiak, Jakub; Fryczkowski, Ryszard; Laska, Jadwiga
ABSTRACT: Articular cartilage dysfunctions are major cause of pain and disability and lead to serious health complications. Cell-based therapies are proposed as treatment methods for cartilage regeneration. In this study, we proposed polyurethane/poly(L-lactide- co -D, L-lactide)-based electrospun nonwovens as carriers for the delivery of human adipose-derived stromal stem cells. We found that 6:4 and 8:2 polyurethane/poly(L-lactide- co -D, L-lactide) initially enhance proliferative rate of human adipose-derived stromal stem cells, shorten their population doubling time, promote creation of functional chondrogenic nodules during chondrogenic differentiation, improve the collagen-2-to-collagen-1 protein ratio, and upregulate the expression of collagen-2 and aggrecan genes. GRAPHICAL ABSTRACT: